ONLINE LEARNING: SHAPING THE FUTURE OF LAW SCHOOLS - Desan Iyer (Obiter, 2022)
The Covid-19 pandemic has wreaked havoc globally and has forced people to change their outlook and do things differently. The pandemic has also affected the education sector. It has brought classes to a halt and forced universities to shut down at times. Significantly, the pandemic has also forced law schools to move away from traditional methods and practices and look for creative ways in which to save the academic year. Inadvertently, it has provided an opportunity to revolutionise and revitalise legal education. As technology becomes ever-present and user-friendly, law schools should embrace the potential of online learning to enhance the value of teaching, expand the learning potential of students and, most importantly, equip students for the challenge of lawyering in the twenty-first century. There are risks and rewards to online learning, but key to education in the new millennium is for law schools to adapt to and embrace online learning with all its challenges. The article provides a cursory general overview of online learning in law schools with specific focus on how law schools have been adapting to online education in recent times. Crucially, the article explores ways in which law schools can overcome key challenges in transitioning to online learning. Going forward, the article looks at how law schools can design and implement online education in a manner that takes advantage of the new modality’s potential.